THE METHOD OF SELF-FILLING OF THE MOLD AT PRODUCTION OF ALUMINIUM CASTINGS - M. A. Sadoha; A. P. Melnikov; V. A. Krajev; A. S. Mironov; V. I. Gutko (Литьë и металлургия, 2004)
The analysis of the ways of improving the quality and reduction of the first cost of the aluminum founding is presented. Different types of the gating systems with the analysis of their advantages and disadvantages are considered. It's shown that the method of founding by self-filling is being especially effective at receiving of long-distance casts. In this case the method of self-filling allows to increase considerably the yield of founding in comparison with the founding into the stationary forms.